2015
DOI: 10.1021/acs.jpcb.5b03608
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Solvation of C60Fullerene by Ionic Liquids II: DFT Analysis of the Interaction Mechanism

Abstract: As a continuation of our previous work (J. Phys. Chem. B, 2014, 118, 11330) on the solvation of C60 by ionic liquids (ILs) using Molecular Dynamic simulations, this paper reports a systematic density functional theory (DFT) analysis on the interaction mechanism between C60 and 24 different ionic liquids (belonging to the imidazolium, piperazinium, and cholinium groups). Properties such as binding energies, charge distributions, intermolecular interactions, or electronic structure were analyzed as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Fullerenes (C60, C180, C240, and C540), graphene, and single-walled nanotubes were described according to the parametrizations reported in a previous work . The interaction of ionic liquids with fullerene was previously characterized for other types of ionic liquids, showing charge transfer due to the ionic liquid–fullerene interaction; therefore, polarization effects were inferred and force fields involving atomic charges considering the charge transfer were used for molecular dynamics simulations. ,, Nevertheless, these force field parametrizations involving polarization effects do not lead to remarkable structural changes. Therefore, because the analysis of structuring is the main objective of the present work, nonpolarizable force fields were used for all simulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fullerenes (C60, C180, C240, and C540), graphene, and single-walled nanotubes were described according to the parametrizations reported in a previous work . The interaction of ionic liquids with fullerene was previously characterized for other types of ionic liquids, showing charge transfer due to the ionic liquid–fullerene interaction; therefore, polarization effects were inferred and force fields involving atomic charges considering the charge transfer were used for molecular dynamics simulations. ,, Nevertheless, these force field parametrizations involving polarization effects do not lead to remarkable structural changes. Therefore, because the analysis of structuring is the main objective of the present work, nonpolarizable force fields were used for all simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the available studies on fullerene + IL considered traditional ILs such as those based on imidazolium cations and fluorinated anions, and the number of studied ILs was very limited. Considering these limitations, our research group reported systematic studies in which the solvation of fullerenes by a large collection of ILs was analyzed using density functional theory (DFT) and molecular dynamics (MD) approaches showing how the IL–fullerene interaction may be fine-tuned through the selection of suitable ions. Another remarkable application involving fullerenes and ILs is the possible encapsulation of these ions inside the fullerene cavity, leading to endohedral fullerenes with IL. Although the experimental development of IL-based endohedral fullerenes has not been reported, a recent theoretical study reported by our group confirmed their suitability …”
Section: Introductionmentioning
confidence: 99%
“…Besides, we follow the recent work by Huang et al 63 and by Cheung et al 64 who utilized the equilibrium bond lengths of fullerene carbon as taken from gas-phase electron diffraction data. 65 Electronic polarizations on the carbon ball as effected by the surrounding polar solvent molecules 44,45,66,67 were not considered.…”
Section: Methodsmentioning
confidence: 99%
“…Room temperature ionic liquids, RTIL, like fullerenes, have long ceased to be exotic compounds, but their combination has been relatively little studied to date. Theoretical studies on C 60 with were performed by Fileti, Chaban, and Maciel [162][163][164][165] and Garcia et al [166,167], whereas Pádua group performed both experimental [168][169][170] and theoretic studies [168].…”
Section: Fullerenes In Room Temperature Ionic Liquids Rtilmentioning
confidence: 99%